Ebola virus disease surveillance and response preparedness in northern Ghana - Martin N. Adokiya; John K. Awoonor-Williams (Taylor & Francis Group, 2016)
Background: The recent Ebola virus disease (EVD) outbreak has been described as unprecedented in terms of morbidity, mortality, and geographical extension. It also revealed many weaknesses and inadequacies for disease surveillance and response systems in Africa due to underqualified staff, cultural beliefs, and lack of trust for the formal health care sector. In 2014, Ghana had high risk of importation of EVD cases. Objective: The objective of this study was to assess the EVD surveillance and response system in northern Ghana. Design: This was an observational study conducted among 47 health workers (district directors, medical, disease control, and laboratory officers) in all 13 districts of the Upper East Region representing public, mission, and private health services. A semi-structured questionnaire with focus on core and support functions (e.g. detection, confirmation) was administered to the informants. Their responses were recorded according to specific themes. In addition, 34 weekly Integrated Disease Surveillance and Response reports (August 2014 to March 2015) were collated from each district. Results: In 2014 and 2015, a total of 10 suspected Ebola cases were clinically diagnosed from four districts. Out of the suspected cases, eight died and the cause of death was unexplained. All the 10 suspected cases were reported, none was confirmed. The informants had knowledge on EVD surveillance and data reporting. However, there were gaps such as delayed reporting, low quality protective equipment (e.g. gloves, aprons), inadequate staff, and lack of laboratory capacity. The majority (38/47) of the respondents were not satisfied with EVD surveillance system and response preparedness due to lack of infrared thermometers, ineffective screening, and lack of isolation centres. Conclusion: EVD surveillance and response preparedness is insufficient and the epidemic is a wake-up call for early detection and response preparedness. Ebola surveillance remains a neglected public health issue. Thus, disease surveillance strengthening is urgently needed in Ghana.